Chloroplast group III twintron excision utilizing multiple 5'- and 3'-splice sites. - Copertino, D W (1992)
The chloroplast genes of Euglena gracilis contain more than 60 group II and 47 group III introns. Some Euglena chloroplast genes also contain twintrons, introns-within-introns. Two types of twintrons have previously been described, a group II twintron and a mixed group II/group III twintron. We report that four introns, three within the RNA polymerase subunit gene rpoC1 and one within ribosomal protein gene rpl16, with mean lengths twice typical group III introns, are a new type of twintron. The group III twintrons are composed of group III introns within other group III introns. The splicing of the twintrons was analyzed by PCR amplification, cloning and sequencing of cDNAs, and Northern hybridization. Excision of each group III twintron occurs by a two-step, sequential splicing pathway. Removal of the internal introns precedes excision of the external introns. Splicing of internal introns in three of the four group III twintrons involves multiple 5'- and/or 3'-splice sites. With two of the twintrons the proximal 5'-splice site can be spliced to an internal 3'-splice site, yielding alternative 'pseudo' fully spliced mRNAs. Excised group III introns of the rpl16 twintron are not linear RNA molecules but either lariat or circular RNAs, probably a lariat. The origins of alternative splicing and a possible evolutionary relationship between group II, group III and nuclear pre-mRNA introns are discussed.